Exploratory analysis of pilot data: Trends of gadget use and psychosocial adjustment in pre-schoolers - Alexander L., Khiu; Hamzah, Hazalizah (Southeast Asia Early Childhood Journal, 2018)
Current mobile media presence in the lives of young children are at an all-time high prompting the need for studies to examine this phenomenon. The current study aims to describe the trends of gadget use and to explore the relationship between gadget use duration and psychosocial adjustment variables among Malaysian pre-schoolers.  The respondents of the current study were 27 parents of pre-schoolers and a majority of the sample were Malays (96.3%). Mean age of parents in this study for mothers (M=35.58, SD=4.45) and fathers (M=36.42, SD=4.58). This study employed the gadget use survey and the Malay version of the Strength and Difficulties Questionnaire (SDQ). It was found that the most commonly available and used device was smartphones and that children mainly used mobile devices for leisure purposes such as watching videos and playing games. An alarming number of children, more than 40%, did not adhere to AAP recommendation of less than 2 hours of media usage daily. A key finding was that the functional relationship between psychosocial adjustment variables and duration of use is curvilinear in nature. However, with a small sample size, caution must be applied, as the findings might not be transferrable to the population.